Sensory marketing and brand positioning of a children's events company - CARRASCO HUIDOBRO, ANGEL; GARCIA TORO, CARLOS; FERNANDEZ OTOYA, FIORELA (LACCEI, 2025)
This study analyzed the relationship between sensory marketing and brand positioning in a children's events company in Chiclayo (Peru). A quantitative, non-experimental, cross-sectional and correlational approach was used, for which 120 clients were surveyed in the last year. To measure sensory marketing and brand positioning, a questionnaire was used and Spearman's Rho correlation coefficient was applied to determine the relationship between these variables. The results showed a positive and significant correlation (0.615), indicating that the application of sensory strategies has a positive influence on brand perception and loyalty.